Seismic landslide hazard assessment using improved seismic motion parameters of the 2017 Ms 7.0 Jiuzhaigou earthquake, Tibetan Plateau - Yang, Zhihua; Du, Guoliang; Zhang, Yangshuang; Xu, Chong; Yu, Pengfei; Shao, Weiwei; Mai, Ximao (Frontiers in Earth Science, 2024)
Seismic landslide hazard assessment plays a very important guiding role during urgent earthquake relief. In August 2017, a Ms 7.0 earthquake in the Jiuzhaigou county, Sichuan province, China triggered thousands of landslides. Based on the analysis of geological settings and coseismic landslide characteristics, the Newmark model is used to complete the seismic landslide hazard assessment. Three seismic motion parameters including peak ground acceleration (PGA), traditional Arias intensity (Arias_P) and improved Arias intensity (Arias_C) are adopted. The publicly published coseismic landslide catalogue is used as validation samples. The results show that the coseismic landslides are mainly distributed in the deep gullies and steep mountainous slopes on the north and south sides of the epicenter. The seismic landslide hazard accuracy based on Arias_C is the best, followed by that based on PGA and Arias_P, respectively. The spatial distribution of seismic landslide hazard based on Arias_C shows an almost standard elliptical ring, and is in good agreement with that of coseismic landslides.These results fully reflect the combined influence of epicenter and seismogenic fault on landslide development. The middle seismic landslide hazard and over are mainly located at areas with seismic intensity VII degree and above. The Arias intensity is very suitable for rapid seismic landslide hazard assessment in emergency situations. The study results can provide scientific and technological support for rapid earthquake relief, and have reference significance for future seismic landslide hazard assessment.